The Phosphoinositide 3‐Kinase Isoform PI3Kβ Regulates Osteoclast‐Mediated Bone Resorption in Humans and Mice. Issue 8 (August 2014) - Győri, Dávid; Csete, Dániel; Benkő, Szilvia; Kulkarni, Suhasini; Mandl, Péter; Dobó‐Nagy, Csaba; Vanhaesebroeck, Bart; Stephens, Len; Hawkins, Phillip T.; Mócsai, Attila
<x xml:space="preserve">Abstract</x> Objective While phosphoinositide 3‐kinases (PI3Ks) are involved in various intracellular signal transduction processes, the specific functions of the different PI3K isoforms are poorly understood. We have previously shown that the PI3Kβ isoform is required for arthritis development in the K/BxN serum–transfer model. Since osteoclasts play a critical role in pathologic bone loss during inflammatory arthritis and other diseases, we undertook this study to test the role of PI3Kβ in osteoclast development and function using a combined genetic and pharmacologic approach. Methods The role of PI3Kβ in primary human and murine osteoclast cultures was tested with the PI3Kβ‐selective inhibitor TGX221 and by using PI3Kβ−/− mice. The trabecular bone architecture of PI3Kβ−/− mice was evaluated using micro–computed tomography and histomorphometric analyses. Results The expression of PI3Kβ was strongly and specifically up‐regulated during in vitro osteoclast differentiation. In vitro development of large multinucleated osteoclasts from human or murine progenitors and their resorption capacity were strongly reduced by the PI3Kβ inhibitor TGX221 or by the genetic deficiency of PI3Kβ. This was likely due to defective cytoskeletal reorganization and vesicular trafficking, since PI3Kβ−/− mouse multinucleated cells failed to form actin rings and retained intracellular acidic vesicles and cathepsin K. In contrast, osteoclast‐specific gene expression and the survival and apoptosis of osteoclasts were not affected. PI3Kβ−/− mice had significantly increased trabecular bone volume and showed abnormal osteoclast morphology with defective resorption pit formation. Conclusion PI3Kβ plays an important role in osteoclast development and function and is required for in vivo bone homeostasis.